Interstellar Pickup Ion Observations to 60 au - D. J. McComas; B. L. Shrestha; G. Livadiotis; J. R. Szalay; E. J. Zirnstein; H. A. Elliott; P. C. Brandt; A. R. Poppe; K. N. Singer; A. Stern; A. Verbiscer; the New Horizons Heliophysics Team (The Astrophysical Journal)
Prior to the Solar Wind Around Pluto (SWAP) observations from New Horizons, the only significant interstellar pickup ion (PUI) observations were taken inside 5.4 au from the Ulysses and 1 au missions. Here, we analyze SWAP data to provide the first comprehensive radial profile of interstellar PUIs in the outer heliosphere from ∼22 to 60 au. This study is the first to combine the low time resolution (one day) data inside 49.5 au with the high time resolution (half hour) data outside of that. We show that these two data sets can be reliably analyzed together in what is now a nearly continuous set of PUI observations. We derive radial gradients for all of the PUI parameters, as well as ratios to their solar wind counterparts from these combined data and extrapolate them out to a nominal termination shock distance at ∼90 au. We find that the fraction of PUIs to all ions in the solar wind continues to grow, reaching ∼18% by 60 au and extrapolated to be ∼30% at 90 au. The PUI internal pressure is ∼11% of the solar wind dynamic pressure at 60 au and expected to be ∼21% by 90 au. Such large values further highlight the importance of PUIs as the dominant driver of the physics of the outer heliosphere, as well as at the termination shock.